Protracted respiratory findings in children post‐SARS‐CoV‐2 infection - Leftin Dobkin, Shoshana C.; Collaco, Joseph M.; McGrath‐Morrow, Sharon A. (Pediatric pulmonology, 2021)
Introduction Although prolonged respiratory symptoms following severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection have been described in adults, data are emerging that children also experience long‐term sequelae of coronavirus disease 2019 (COVID‐19). The respiratory sequelae of COVID‐19 in children remain poorly characterized. In this study we describe health data and respiratory findings in pediatric patients presenting with persistent respiratory symptoms following COVID‐19. Methods This study included patients referred to Pulmonary Clinic at the Children's Hospital of Philadelphia between December 2020 and April 2021 (n = 29). Inclusion criteria included a history of SARS‐CoV‐2 RNA positivity or confirmed close household contact and suggestive symptoms. A retrospective chart review was performed and demographic, clinical, imaging, and functional test data were collected. Results The mean age at presentation to clinic was 13.1 years (range: 4–19 years). Patients had persistent respiratory symptoms ranging from 1.3 to 6.7 months postacute infection. Persistent dyspnea and/or exertional dyspnea were present in nearly all (96.6%) patients at the time of clinic presentation. Other reported chronic symptoms included cough (51.7%) and exercise intolerance (48.3%). Fatigue was reported in 13.8% of subjects. Many subjects were overweight or obese (62.1%) and 11 subjects (37.9%) had a prior history of asthma. Spirometry and plethysmography were normal in most patients. The six‐minute walk test (6MWT) revealed exercise intolerance and significant tachycardia in two‐thirds of the nine children tested. Conclusion Exertional dyspnea, cough and exercise intolerance were the most common respiratory symptoms in children with postacute COVID‐19 respiratory symptoms seen in an outpatient pulmonary clinic. Spirometry (and plethysmography when available), however, was mostly normal, and exertional intolerance was frequently demonstrated using the 6MWT.